Overcoming physical dormancy in seeds of Jatropha mollissima (Pohl) Baill. (Euphorbiaceae) in the semiarid region of Brazil - Lyra, Danilo Hottis; Almeida, Lucas Aragão da Hora; Brasileiro, Bruno Portela; Amaral, Cláudio Lúcio Fernandes (MAGISTRA, 2017)
Abstract: Jatropha mollissima (Pohl) Baill is a shrub species native of Caatinga biome; it has great medicinal, oleaginous and ornamental potential. Seed dormancy is considered a very common adaptive plant strategy in unpredictable and harsh environments. The aim of this study was to evaluate the effects of different pre-germination treatments on overcoming physical dormancy in seeds of Jatropha mollissima. The treatments adopted to overcome dormancy were: T1 - control; T2 - mechanical scarification on the opposing extremity to hilum with sandpaper No 80; T3 - mechanical scarification on the lateral region with sandpaper No 80; T4 - immersion in water at 25 ºC for 24 hours; T5 - water immersion at 25 ºC for 12 hours; T6 - water immersion at 100 ºC for one minute. The seedling vigor traits evaluated were percentage of emergency, emergency speed index, length of the aerial part and root, dry weight matter of the aerial part and root, steam diameter and number of leaves. The treatment T6 showed no seedlings emergency. J. mollissima seeds have tegumentary dormancy. The results showed that the most efficient treatments to overcome physical dormancy of J. mollissima seeds were the mechanical scarification on the opposing extremity to hilum and the lateral region. Keywords: Pinhão-Bravo, Germplasm and Caatinga.